Translation and adaptation of the Competencias Esenciales en Salud Pública para los recursos humanos en salud - Maria de Lourdes de Almeida; Aida Maris Peres; Maria Manuela Frederico Ferreira; Maria de Fátima Mantovani
ABSTRACT Objective: to perform the translation and cultural adaptation of the document named Marco Regional de Competencias Esenciales en Salud Pública para los Recursos Humanos en Salud de la Región de las Américas (Regional Framework of Core Competencies in Public Health for Health Human Resources in the Region of Americas) from Spanish to Brazilian Portuguese. Method: a methodological study comprising the following phases: authorization for translation; initial translation; synthesis of translations and consensus; back-translation and formation of an expert committee. Result: in the translation of domain names, there was no difference in 66.7% (N = 4); in the translation of domain description and competencies there were divergences in 100% of them (N = 6, N = 56). A consensus of more than 80% was obtained in the translation and improvement in the expert committee by the change of words and expressions for approximation of meanings to the Brazilian context. Conclusion: the translated and adapted document has the potential of application in research, and use in the practice of collective/public health care in Brazil.